Buffering effect of chicken skin and meat protects salmonella enterica strains against hydrochloric acid but not organic acid treatment - Tan, S.; Lee, S.; Dykes, Gary (2014)
This study investigated the buffering effect of chicken skin and meat by determining changes in the pH of phosphate buffered saline solutions (PBS; pH 2, 3, 5, 7, 9 and 11) before and after incubation at refrigeration temperature with these two chicken components. In addition, the effects of organic acids and hydrochloric acid on the survival of two strains each of Salmonella Typhimurium and Salmonella Enteritidis inoculated onto chicken skin and meat were determined. The Salmonella strains were enumerated before and after exposure to acid treatment and compared to Salmonella in PBS without chicken. Chicken meat buffered better than chicken skin and, for example, increased the pH 2 PBS to pH 4.8 (p < 0.001). Of the four acids acetic acid most rapidly reduced numbers of Salmonella on chicken, followed by citric acid, lactic acid and HCl. Acetic acid, lactic acid, citric acid and HCl effectively eliminated Salmonella at ~ pH 3.8 (p < 0.001), ~pH 2.5 (p < 0.05), ~pH 2.9 (p < 0.05) and ~pH 1.2 (p < 0.001), respectively. The buffering effect of chicken protected Salmonella against HCl at pH 2 but not from organic acids at the same pH. The ability of acetic acid to eliminate Salmonella on chicken meat at ~ pH 4 suggests it has potential for application in commercial marination.